2014
DOI: 10.1007/s00246-014-1065-5
|View full text |Cite
|
Sign up to set email alerts
|

Early Results of Neurodevelopment Following Hybrid Stage I for Hypoplastic Left Heart Syndrome

Abstract: Motor skills and neurodevelopment in infants with hypoplastic left heart syndrome (HLHS) who have undergone Hybrid Stage I palliation is unknown. The purpose of this study is to assess early neurodevelopment in infants with HLHS after Hybrid Stage I palliation. Developmental assessment was performed in HLHS infants who underwent Hybrid Stage I palliation at 2 and 4 months of age using the Test of Infant Motor Performance, and at 6 months of age, prior to undergoing the second staged surgery, using the Bayley S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 40 publications
2
41
1
Order By: Relevance
“…reported that 76% of their study cohort did not complete pre‐operative neurobehavioural assessment due to medical contraindications. Numerous other prospective cohort studies have reported similar challenges to obtaining baseline data consequently limiting their ability to determine the prevalence of abnormalities prior to surgery and the impact of intra‐operative risk factors. The ACC score correlates with post‐operative length of stay and mortality prior to discharge .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that 76% of their study cohort did not complete pre‐operative neurobehavioural assessment due to medical contraindications. Numerous other prospective cohort studies have reported similar challenges to obtaining baseline data consequently limiting their ability to determine the prevalence of abnormalities prior to surgery and the impact of intra‐operative risk factors. The ACC score correlates with post‐operative length of stay and mortality prior to discharge .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, participant attrition and missing data are universal threats to longitudinal studies. Studies with small sample sizes and missing data limit the predictive validity of findings and create significant challenges for investigators . These challenges are amplified when studying medically fragile, at‐risk infants during the vulnerable time between birth and open heart surgery.…”
mentioning
confidence: 99%
“…Knirsch and colleagues [61] could not identify any effect of the respective hybrid versus Norwood surgical strategy on neurodevelopmental outcome assessed with standardized neuromotor examination and the Bayley Scales of Infant Development II through follow-up at age 4 years [63]. Similar to Norwood patients, hybrid patients showed signs of significant neurodevelopmental delay before [62] or after comprehensive stage II [61]. So far, there is no evidence that hybrid palliation has a protective or detrimental effect on the neonatal brain compared with Norwood palliation.…”
Section: Neurodevelopmental Outcomementioning
confidence: 97%
“…Several studies have assessed neurodevelopmental outcome of patients palliated with the hybrid strategy [61,62]. Knirsch and colleagues [61] could not identify any effect of the respective hybrid versus Norwood surgical strategy on neurodevelopmental outcome assessed with standardized neuromotor examination and the Bayley Scales of Infant Development II through follow-up at age 4 years [63].…”
Section: Neurodevelopmental Outcomementioning
confidence: 99%
“…Similar to findings in previous developmental studies in children who had a Norwood palliation, motor impairment was high. 40 In another study, 41 infants with HLHS who underwent hybrid stage I palliation and normal, healthy, age-matched controls were compared. The HLHS group scored lower than the control group in motor skills, language, and cognitive development as indicated by scores on the Bayley Scales of Infant and Toddler Development.…”
Section: Developmental Outcomesmentioning
confidence: 99%